(3EfHGg GdCfHGg Ydi JMbjb EYQGH dG Gdg GdG Gddgs - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s ((3eMeO SYjO Hf YHO GdZfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fUH ai GdBaGb hGdCfaS Ydi hMOGfjI CeG HYO agPG CjgG GdPci GdeJhbO gh Gdbhd GdSOjO GdeYQH YeG jJYdb HcdeI GdJhMjO eeG eYXeg GdcdGe ai GdEYQGH s
(3BNQgG (B:s
(3hUd Gddge Ydi SjOfG eMeO hSde hYdi Bdg hUMHg CLejYf hGdMeO ddg QH GdYGdejf Je cJGH EfHGg GdCfHGg Ydi JMbjb EYQGH dG Edg GdG Gddg s
(3GdfSNI edMbI HKdGK hQbGJ ef GdeNWhW ETJedJ Ydi GdeHMK GdChd hGdKGfi HHOGjI hfgGjI LOjOIs
(3fSNI eLOhdI HGdPgHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
Keywords: (3GdfMhs